Lumbar Neuraxial Procedures in Thrombocytopenic Patients Across Populations: A Systematic Review and Meta-analysis. Issue 3 (September 2020) - Bauer, M.E.; Toledano, R.D.; Houle, T.; Beilin, Y.; MacEachern, M.; McCabe, M.; Rector, D.; Cooper, J.P.; Gernsheimer, T.; Landau, R.; Leffert, L.
Abstract : ( J Clin Anesth . 2020;61:109666) Presently, there is no agreement among experts in regards to the safe minimum threshold platelet count for lumbar neuraxial anesthetic procedures, as there are limited data available on neuraxial anesthetic procedures performed on thrombocytopenic patients. During cesarean deliveries, there are important maternal and fetal factors and side effects to consider when choosing to administer general anesthesia rather than neuraxial anesthesia. Because more data on spinal epidural hematoma are needed, Bauer and colleagues conducted this systematic review to assemble reported lumbar neuraxial procedures (lumbar puncture; spinal, epidural, or combined spinal-epidural analgesia/anesthesia; epidural catheter removal) from various thrombocytopenic populations to bring some clarity to the risk of spinal epidural hematoma.